2008
DOI: 10.1016/j.jacc.2007.08.062
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the Index of Microcirculatory Resistance in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: Compared to standard measures, IMR appears to be a better predictor of microvascular damage after STEMI, both acutely and in short term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
229
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 268 publications
(251 citation statements)
references
References 26 publications
(23 reference statements)
17
229
3
2
Order By: Relevance
“…6 In addition, Fearon demonstrated that, compared to other traditional methods for assessing the microvasculature, IMR appears to be a better predictor of microvascular damage and recovery of left ven-ITO N et al tricular function after ST-segment elevation MI (STEMI). 7 Although microvascular injury following PCI can be evaluated with IMR, no method of treatment has been established. Several groups have shown that coronary microvascular resistance is predominantly regulated by adenosine triphosphate-sensitive potassium (K-ATP) channels.…”
mentioning
confidence: 99%
“…6 In addition, Fearon demonstrated that, compared to other traditional methods for assessing the microvasculature, IMR appears to be a better predictor of microvascular damage and recovery of left ven-ITO N et al tricular function after ST-segment elevation MI (STEMI). 7 Although microvascular injury following PCI can be evaluated with IMR, no method of treatment has been established. Several groups have shown that coronary microvascular resistance is predominantly regulated by adenosine triphosphate-sensitive potassium (K-ATP) channels.…”
mentioning
confidence: 99%
“…In patients undergoing coronary stenting for stable angina and ST-elevation MI (STEMI), stent placement was found to cause microvascular injury as evaluated by IMR. [20][21][22] Previous data from Melikian, et al suggest that there is large overlap in IMR values between patients with or without epicardial atherosclerosis. Impact of smoking on coronary physiology: The finding that among patients with CAD, smokers had greater IMR than nonsmokers, suggests that smoking adversely affects coronary microcirculatory resistance.…”
Section: Discussionmentioning
confidence: 99%
“…IMR corresponds with the extent of coronary microvasculature disruption in humans,6 and is stable and reproducible in the presence of varying hemodynamic conditions 7. In earlier studies, IMR measured immediately after primary PCI correlated with myocardial infarct size as measured by peak creatine kinase, whereas other less quantitative or specific measures of the microcirculation (including TIMI myocardial perfusion grade, TIMI frame count, coronary flow reserve, and ST‐segment resolution) did not 8. An IMR >32 U has also been associated with worse wall motion score on echocardiogram 3 months post STEMI.…”
Section: Introductionmentioning
confidence: 93%